Controversial issues in vitiligo patients: a review of old and recent treatments. Issue 1 (21st October 2018) - Lotti, Torello; Gianfaldoni, Serena; Valle, Yan; Rovesti, Miriam; Feliciano, Claudio; Satolli, Francesca
Abstract: Vitiligo is quite a common hypopigmentary disorder, which may affect both children and adults with important psychological effects due to the well‐known leopard skin‐like appearance. The authors summarize in the present study the published evidence on vitiligo with particular interest on the controversial aspects of the disease, such as its definition and the available treatments.